Important Technologies and Effective Methods for Teaching History and Historical Disciplines (Texas Journal of Philology, Culture and History, 2023)
A history teacher or a specialist in the human science, when lecturing or speaking to an audience, wants to have not only a competent, free, structured, delivered speech, but also that the material is entertaining, relevant and accessible to listeners or students. This article will consider the second aspect and its important components. Additionally, it can be noted, that this article being a review, may be useful to teachers or those who are interested in the methodology of teaching history.